Surgical Innovations in Glaucoma - Samples, John R.; Ahmed, Iqbal Ike K. (Springer New York : Imprint: Springer, 2014)
There is a revolution in new glaucoma surgical techniques. New glaucoma surgical devices are taking precedence in glaucoma surgery, with the new surgeries drastically cutting down on the chances for patient infection as well as higher success rates compared to the older types of surgery.   Surgical Innovations in Glaucoma is the only book of its kind written by the top experts in the field, from inventors, clinical trial investigators, and top specialists experienced with the new devices. Written for general ophthalmologists who perform glaucoma surgery, the text walks the reader through the what, where, when, and how of the new glaucoma surgical tools, and includes supplementary online how-to videos for those interested in seeing the latest glaucoma procedures performed with these devices.